2019
DOI: 10.3390/ijerph16050891
|View full text |Cite
|
Sign up to set email alerts
|

Behaviors and Attitudes of Polish Health Care Workers with Respect to the Hazards from Blood-Borne Pathogens: A Questionnaire-Based Study

Abstract: Blood-borne infections represent an important occupational health issue in health care settings. The aim of this study was to analyze behaviors of health care workers (HCWs) in the field of needlestick injuries (NSIs) as well as to learn about their attitudes to patients infected with blood-borne viruses. A total of 487 HCWs based at 26 hospitals in Poland completed an anonymous self-administered questionnaire in the period of October–December 2015. Data was analyzed using descriptive statistics and multiple l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 31 publications
3
29
1
3
Order By: Relevance
“…These findings are consistent and similar to the Bosnia/Herzegovinian, Cameroonian, Saudi Arabian studies on risk of occupational exposure conducted [9][12] [13]. On the contrary, higher prevalence of occupational exposure to HIV infection among health care workers than the prevalence found in the current study has been reported by several other researchers in sub-Saharan Africa and other parts of the world [14].But, our findings on prevalence of occupational exposure are above that obtained from similar studies conducted in Poland [8] ,Kuwait [15] , South Korea [16] and Northern Nigeria [17].This difference in prevalence of HIV observed in previous studies and our present study could be as a result of the difference in the study setting, study design and other methodological techniques. The differential in the level of training received by the health care workers in different study settings could also contribute to the variation.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These findings are consistent and similar to the Bosnia/Herzegovinian, Cameroonian, Saudi Arabian studies on risk of occupational exposure conducted [9][12] [13]. On the contrary, higher prevalence of occupational exposure to HIV infection among health care workers than the prevalence found in the current study has been reported by several other researchers in sub-Saharan Africa and other parts of the world [14].But, our findings on prevalence of occupational exposure are above that obtained from similar studies conducted in Poland [8] ,Kuwait [15] , South Korea [16] and Northern Nigeria [17].This difference in prevalence of HIV observed in previous studies and our present study could be as a result of the difference in the study setting, study design and other methodological techniques. The differential in the level of training received by the health care workers in different study settings could also contribute to the variation.…”
Section: Discussionsupporting
confidence: 77%
“…This study focuses on how health care workers are at higher risk of occupational infection compared to other healthcare workers in non-HIV specialised facilities [8]. It also focuses on specialized HIV care centres such as Prevention of Maternal to Child Transmission of HIV (PMTCT) sites in public and private settings [9].…”
mentioning
confidence: 99%
“…This study focuses on how health care workers are at higher risk of occupational infection compared to other healthcare workers in non-HIV specialised facilities [10]. It also focuses on specialized HIV care centres such as Prevention of Maternal to Child Transmission of HIV (PMTCT) sites in public and private settings [11].…”
Section: Introductionmentioning
confidence: 99%
“…[ Figure 2 is here] 8 The main predictors of occupational exposure to HIV were career cadre. Doctors were more likely to have occupational exposure to HIV than another worker (AOR=2.2, 95% C.I=1.2-4.3, p<0.05).…”
Section: Resultsmentioning
confidence: 99%
“…This study focuses on health care workers at higher risk of occupational infection compared to other healthcare workers in non-HIV specialised facility [8] . It also focuses on specialized HIV care centre such as Prevention of Maternal to Child Transmission of HIV (PMTCT) sites in public and private setting [9].…”
mentioning
confidence: 99%